Ask a New Question
Search
Simplify the expression (tanθ+cotθ)^2 - (tanθ-cotθ)^2 using algebra and trigonometric identities.
1 answer
(tanθ+cotθ)^2 - (tanθ-cotθ)^2
= (tan^2θ + 2 + cot^2θ) - (tan^2θ - 2 + cot^2θ)
= 4
because tanθ cotθ = 1
Ask a New Question
or
answer this question
.
Similar Questions
Find the exact value of cotθ given secθ=3 and tanθ<0.
cotθ=8√/3 cotθ=−(3/√8) cotθ=1/√8 cotθ=−(√8/3)
3 answers
For the acute angle θ, given that sinθ=1/7, find the exact value of cotθ.
cotθ=1/√48 cotθ=1/√50 cotθ=√50 cotθ=√48
1 answer
Two charged spheres of charge q and mass m are each hanging from strings and are at equilibrium as shown below:
Give an
1 answer
Blake is told that an angle has a cosine of −16√
and is in Quadrant III. Use the Pythagorean identity sin2(θ)+cos2(θ)=1 ,
1 answer
more similar questions